2016
DOI: 10.1101/gad.281410.116
|View full text |Cite
|
Sign up to set email alerts
|

Chronic AMPK activation via loss of FLCN induces functional beige adipose tissue through PGC-1α/ERRα

Abstract: The tumor suppressor folliculin (FLCN) forms a repressor complex with AMP-activated protein kinase (AMPK). Given that AMPK is a master regulator of cellular energy homeostasis, we generated an adipose-specific Flcn (Adipoq-FLCN) knockout mouse model to investigate the role of FLCN in energy metabolism. We show that loss of FLCN results in a complete metabolic reprogramming of adipose tissues, resulting in enhanced oxidative metabolism. Adipoq-FLCN knockout mice exhibit increased energy expenditure and are prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
82
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 48 publications
10
82
0
Order By: Relevance
“…A recent study (Yan et al 2016) also reported on the phenotype of adipose-specific deletion of FLCN using the same genetic model of adiponectin-Cre to delete FLCN in adipose cells. The study reported that FLCN deletion in fat leads to browning of adipose tissue, cold resistance, obesity resistance upon high-fat diet challenge, and improved glucose metabolism.…”
Section: Tfe3 As a Hub For Adipose Tissue Browningmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study (Yan et al 2016) also reported on the phenotype of adipose-specific deletion of FLCN using the same genetic model of adiponectin-Cre to delete FLCN in adipose cells. The study reported that FLCN deletion in fat leads to browning of adipose tissue, cold resistance, obesity resistance upon high-fat diet challenge, and improved glucose metabolism.…”
Section: Tfe3 As a Hub For Adipose Tissue Browningmentioning
confidence: 99%
“…5,6). It is possible that the FLCN-AMPK pathway proposed by Yan et al (2016) superimposes on this pathway by modulating mTOR/TFE3. A recent report (Young et al 2016) showed in embryoid bodies that AMPK promotes the activity of TFEB, a molecule highly homologous to TFE3, and that this regulation of TFEB by AMPK occurs at least partly through mTOR.…”
Section: Tfe3 As a Hub For Adipose Tissue Browningmentioning
confidence: 99%
“…Adipose tissue function is controlled by several processes including mitochondrial biogenesis, adaptive thermogenesis, mitochondrial fatty acid oxidation, oxygen consumption and oxidative phosphorylation that are regulated by PGC-1α [23], [24], [25]. Adipocytes store fat and excess energy, however, beige and brown adipocytes are regarded as the major source of mitochondrial and thermogenic function to combat obesity and metabolic syndrome [23], [26].…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes store fat and excess energy, however, beige and brown adipocytes are regarded as the major source of mitochondrial and thermogenic function to combat obesity and metabolic syndrome [23], [26]. Several transcriptional factors regulate the levels of signaling molecules that are involved in the expression of thermogenic and mitochondrial function in beige and visceral fat [23], [25], [26], [27], [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…Cold and energy stress also induce the stress-activated protein kinase AMP-activated protein kinase (AMPK), which enhances EE and thus is a major target in obesity and T2D (19)(20)(21)(22)(23)(24). β-ARmediated AMPK activation augments insulin sensitivity in a UCP1-dependent manner (22).…”
Section: Introductionmentioning
confidence: 99%